KINERJA GURU PADA MAN BEUREUGHANG KABUPATEN ACEH UTARA DALAM KEMAMPUAN KERJA - Bahagia, Muhammad (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2023)
This research aims to analyze performance data  teacher of MAN Beureughang in workability.This research uses a qualitative approach. Data in this research is can be grouped into two data source that is: Primary data that consist of the representation of teacher of civil servant who teaches at MAN Beuregang Regency of North Aceh. Secondary data that is data of Beureunghang teacher workability in North Aceh Regency. The data source is 6 civil servant civil servants (PNS) who become the permanent lecturer at MAN Beureughang of North Aceh Regency. Data collection techniques with structured interviews, observation, and documentation. The data analysis in this study follows the concept given by Miles and Huberman. Miles and Huberman revealed that the activity in qualitative data analysis is done interactively and continuously in every stage of the research so that it is complete. The results of the research indicate that the performance of MAN Beureughang teachers in North Aceh Regency in the workability is not good and still needs improvements in order to get in the right direction.